Все изменит поцелуй: Роман / Э. Бойл ; пер. с англ. А. В. Рубина - Бойл Элизабет (Очарование, 2003)
Экземпляры: б/ф-8 (20101101) / Инвентарный номер: 25864 / Цена: 55.00 / Авт.знак: Б 77 / ББК: 84(7Сое)